Intradural Lipoma at the Craniocervical Junction Presenting with Progressing Hemiparesis: A Case Report - Takuro Inoue; Hisao Hirai; Ayako Shima; Fumio Suzuki; Masayuki Matsuda; Takanori Fukushima (Case Reports in Neurology, 2019)
Intradural spinal lipomas are rare in an adult population. They are mostly asymptomatic and usually associated with spinal dysraphism in a pediatric population. We report a rare case of spinal lipoma without dysraphism and with progressing hemiparesis. A 60-year-old woman had incidental lipoma at the craniocervical junction observed for more than 5 years. Recently, she developed right-sided hemiparesis and sensory disturbance. Radiological studies revealed a large lipoma compressing the dorsal medulla and C1–C2 spinal cord. Standard midline suboccipital craniotomy and C1 laminectomy were performed, and the lipoma was removed subtotally. The lipoma showed severe adhesion to the dorsal medulla and C1 spinal cord; therefore, the excision was limited as internal debulking. Her neurological deficit subsided within 6 months after the decompressive surgery. Considering the benign nature of lipoma, internal decompression is a reasonable management for this lesion.